Cardiac Imaging for the Assessment of Left Atrial Mechanics Across Heart Failure Stages - Bandera, Francesco; Mollo, Anita; Frigelli, Matteo; Guglielmi, Giulia; Ventrella, Nicoletta; Pastore, Maria Concetta; Cameli, Matteo; Guazzi, Marco (Frontiers in Cardiovascular Medicine, 2022)
Left atrium (LA) is emerging as a key element in the pathophysiology of several cardiac diseases, having an active role in contrasting heart failure (HF) progression. Its morphological and functional remodeling occurs progressively according to pressure or volume overload generated by the underlying disease and its ability of adaptation contributes to avoid pulmonary circulation congestion and to postpone HF symptoms. Moreover, early signs of LA dysfunction can anticipate and predict the clinical course of HF diseases before the symptoms onset, also in patients at increased risk of HF with still normal cardiac structure (stage A HF). The study of LA mechanics (chamber morphology and function) is moving from a research interest to a clinical application thanks to a great clinical, prognostic and pathophysiological significance. This process is promoted by the technological progress of cardiac imaging which increases the availability of easy-to-use tools for clinicians and HF specialists. 2D speckle tracking echocardiography and feature tracking cardiac magnetic resonance are becoming essential for daily practice. In this context, a deep understanding of LA mechanics, its prognostic significance and the available approaches are essential to improve clinical practice. The present review will focus on LA mechanics, discussing atrial physiology and pathophysiology of main cardiac diseases across the HF stages, with specific attention to the prognostic significance. Imaging techniques for LA mechanics assessment will be discussed, with an overlook on the dynamic (under stress) evaluation of the chamber.